Development and Implementation of XR Virtual Edu: Platform for Teacher Training in Immersive Technologies. - Guterres, Lisandra Xavier; Ribeiro, Luis Otoni Meireles; Bederode, Igor Radtke; Vergara, Ildaiane Pintanela (DAT Journal, 2026)
The growing use of immersive digital technologies, such as Virtual Reality (VR) and Augmented Reality (AR), promoted by the evolution of mobile devices, offers a transformative potential for education, allowing a more active learning experience, through the interaction of the student with the object of study in an immersive and interactive way. Based on this, this article aims to present the process of creating the XR Virtual Edu website, which helps teachers to incorporate immersive digital technologies into their educational contexts through MOOC courses. Due to the need to combine pedagogical, content and technological aspects to train teachers in the development of solutions with AR and VR, TPACK, Design Thinking and Microlearning were used as theoretical and methodological bases. Finally, XR Virtual Edu presents itself as a potential tool for training teachers in the use of immersive technologies in the teaching-learning process.